Clinico-Epidemiological Study of Self-Poisoning by Different Pharmaceutical Agents - Ahmed, Habib; Rahman, Ferdousi; Rahman, Mahbubur; Karim, Mohammad Enamul; Rahim, Sayeda; Rowshon, AHM; Faiz, MA (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: In Bangladesh self-poisoning cases are mostly of organophosphorous compound (OPC). It is documented that 14% of all deaths amongst 10 to 50 year old women in Bangladesh were due to poisoning, the majority following suicidal ingestion of pesticides. In tertiary level hospital, a large number of self-poisoning cases are of different pharmaceutical agents, mostly from urban areas and mostly of teenager group. So the trend of self-poisoning is different in urban area than that of rural area. These pharmaceutical agent self-poisoning cases admitted into the hospitals have different modalities of clinical features with variable outcomes and socioeconomic background. But there is no actual data of these self-poisoning by the different pharmaceutical agents. Therefore, this study was aimed to describe the pattern of self-poisoning by different pharmaceutical agents. Methods: A descriptive longitudinal study was conducted in five adult medicine units of a tertiary level hospital from January 2008 to June 2008. All self-poisoned patients with different pharmaceutical agents were included with their prior informed written consent. A pre-tested questionnaire was used for data collection. Results: A total of 281 patients were interviewed. Most of the patients were female (70.8%) with highest age range from 13 to 30 years (91.81%). Most of the patients were students (53%) and 40.9% were secondary school certificate pass. 60.1% patients were unmarried. Most of the patients were from urban area (84%). The commonest background for self-poisoning was family disharmony (74.46%). Most common offending pharmaceutical agents were benzodiazepines (44.10%), collected mostly from local dispensary without prescription (89.33%). Most of the patients consulted within 1 to 2 hours of poisoning (44.5%). Commonest consultation before admission was in a Government hospital (48.40%). Only 3 patients (1.10%) were known to have psychiatric illness. Five patients (1.80%) had previous history of self-poisoning. Most of the patients (89.3%) stayed in the hospital for 1 day with no mortality. Conclusion: Self poisoning by pharmaceutical agents is common especially in urban areas. Common offending pharmaceutical agents were benzodiazepines. The commonest background for self-poisoning was family disharmony. J Shaheed Suhrawardy Med Coll, June 2016, Vol.8(1); 17-22